The new way things work - Macaulay, David; Ardley, Neil. (Boston : Houghton Mifflin, 1998)
Text and numerous detailed illustrations introduce and explain the scientific principles and workings of hundreds of machines. Includes new material about digital technology.
"Originally published as The way things work"--T.p. verso.
"Published in Great Britain by Dorling Kindersly Limited"--T.p. verso.
Includes index.
Wilson's Children
Wilson's Junior High School
Wilson's Senior High School
Keywords: Technology -- Popular works; Technology; Technology